Dynamics of Male and Female Social Interactions in Students with Intellectual Disabilities during Puberty - Zainab Al Ghazali; Nur Azizah; Hermanto Hermanto; Mulina M. Cabatay (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
This research aimed to determine the understanding and experiences of students with intellectual disabilities regarding social interactions of the opposite gender during puberty. The focus was on comprehending these interactions and identifying associated risk and protective factors. A qualitative method was used, incorporating the Miles and Huberman analysis model as well as triangulating data through interviews and observations. The results showed that students with intellectual disabilities tended to imitate social interaction behaviors of the opposite gender observed in the surroundings including media such as TV and YouTube. Schools also played an important role in managing the protective factors within these interactions for students with intellectual disabilities. Measures implemented included reproductive health training, assigning proactive teachers to students, providing education on the boundaries of social interactions of the opposite gender, and installing CCTV to monitor and prevent negative behaviors. The actions were intended to mitigate the adverse effects of social interactions, particularly those including opposite-gender relationships.